DAYA TANGGAP, JAMINAN, BUKTI FISIK, EMPATI, KEHANDALAN, DAN KEPUASAN PASIEN - Amalia, Afni; Tua R.F.S, Harapan; Rusli, Zaili (Jurnal Ilmu Administrasi Negara, 2018)
Responsiveness, Assurance, Tangible, Emphaty, Reliability, and Patient Satisfaction. The purpose of this study is to analyzing the influence of responsiveness, assurance, tangible, emphaty, and reliability to patient satisfaction BPJS Kesehatan outpatient at Rumah Sakit Umum Daerah Arifin Achmad in Pekanbaru. This research is a quantitative research. The population in this study were 10 highest polyclinic patients BPJS Kesehatan outpatient RSUD Arifin Achmad Pekanbaru 2016 amounted to 83,711 people, while the sample amounted to 100 respondents with the sampling method used is accidental sampling. The statistical method used to test the research hypotheses is multiple regression by using SPSS 21. The result of this study indicated that variable assurance, tangible, and reliability significantly affect to patient satisfaction, but the variable responsiveness and emphaty don’t significantly affect to satisfaction. Different simultaneously, indicating that responsiveness, assurance, tangible, emphaty, and reliability together have a significantly affect on patient satisfaction. The effect of adjusted R2 from responsiveness, assurance, tangible, empathy, and reliability to patient satisfaction was 61,2%, while the remaining 38,8% is influenced by other variables outside the model not been included in this study.